One-pot synthesis of oxazolidinones and five-membered cyclic carbonates from epoxides and chlorosulfonyl isocyanate: theoretical evidence for an asynchronous concerted pathway - Demir, Esra; Sari, Ozlem; Çetinkaya, Yasin; Atmaca, Ufuk; Sağ Erdem, Safiye; Çelik, Murat (Beilstein Journal of Organic Chemistry, 2020)
The one-pot reaction of chlorosulfonyl isocyanate (CSI) with epoxides having phenyl, benzyl and fused cyclic alkyl groups in different solvents under mild reaction conditions without additives and catalysts was studied. Oxazolidinones and five-membered cyclic carbonates were obtained in ratios close to 1:1 in the cyclization reactions. The best yields of these compounds were obtained in dichloromethane (DCM). Together with 16 known compounds, two novel oxazolidinone derivatives and two novel cyclic carbonates were synthesized with an efficient and straightforward method. Compared to the existing methods, the synthetic approach presented here provides the following distinct advantageous: being a one-pot reaction with metal-free reagent, having shorter reaction times, good yields and a very simple purification method. Moreover, using the density functional theory (DFT) method at the M06-2X/6-31+G(d,p) level of theory the mechanism of the cycloaddition reactions has been elucidated. The further investigation of the potential energy surfaces associated with two possible channels leading to oxazolidinones and five-membered cyclic carbonates disclosed that the cycloaddition reaction proceeds via an asynchronous concerted mechanism in gas phase and in DCM.
Keywords: chlorosulfonyl isocyanate; computational modeling; cyclic carbonates; density functional theory; oxazolidinone

(untitled) - Stevens, D. L.; Dotter, B.; Madaras-Kelly, K. (Expert Rev. Anti-Infect. Ther., 2004)

(untitled) - Wang, J.; Xia, L.; Wang, R.; Cai, Y. (Front. Pharmacol., 2019)

(untitled) - Barbachyn, M. R.; Ford, C. W. (Angew. Chem., Int. Ed., 2003)

(untitled) - Orac, C. M.; Zhou, S.; Means, J. A.; Boehm, D.; Bergmeier, S. C.; Hines, J. V. (J. Med. Chem., 2011)

(untitled) - Ager, D. J.; Prakash, I.; Schaad, D. R. (Chem. Rev., 1996)

(untitled) - Flynn, B. L.; Manchala, N.; Krenske, E. H. (J. Am. Chem. Soc., 2013)

(untitled) - Wan, N.; Zhou, X.; Ma, R.; Tian, J.; Wang, H.; Cui, B.; Han, W.; Chen, Y. (Adv. Synth. Catal., 2020)

(untitled) - Narina, S. V.; Kumar, T. S.; George, S.; Sudalai, A. (Tetrahedron Lett., 2007)

(untitled) - Asano, M.; Nagasawa, C.; Suzuki, M.; Nishiyama, S.; Sugai, T. (Biosci., Biotechnol., Biochem., 2005)

(untitled) - Xin, Q.; Fan, H.; Guo, B.; He, H.; Gao, S.; Wang, H.; Huang, Y.; Yang, Y. (J. Med. Chem., 2011)

(untitled) - Zhanel, G. G.; Love, R.; Adam, H.; Golden, A.; Zelenitsky, S.; Schweizer, F.; Gorityala, B.; Lagacé-Wiens, P. R. S.; Rubinstein, E.; Walkty, A.; Gin, A. S.; Gilmour, M.; et al. (Drugs, 2015)

(untitled) - Mai, A.; Artico, M.; Esposito, M.; Ragno, R.; Sbardella, G.; Massa, S. (Farmaco, 2003)

(untitled) - Youdim, M. B. H.; Edmondson, D.; Tipton, K. F. (Nat. Rev. Neurosci., 2006)

(untitled) - Gunal, S. E.; Tuncel, S. T.; Kelekci, N. G.; Ucar, G.; Dursun, B. Y.; Erdem, S. S.; Dogan, I. (Bioorg. Chem., 2018)

(untitled) - Buckler, J. N.; Meek, T.; Banwell, M. G.; Carr, P. D. (J. Nat. Prod., 2017)

(untitled) - Peña-López, M.; Neumann, H.; Beller, M. (Eur. J. Org. Chem., 2016)

(untitled) - Comerford, J. W.; Ingram, I. D. V.; North, M.; Wu, X. (Green Chem., 2015)

(untitled) - Aravindan, V.; Gnanaraj, J.; Madhavi, S.; Liu, H.-K. (Chem. – Eur. J., 2011)

(untitled) - Tezuka, K.; Koda, K.; Katagiri, H.; Haba, O. (Polym. Bull., 2015)

(untitled) - Azechi, M.; Matsumoto, K.; Endo, T. (J. Polym. Sci., Part A: Polym. Chem., 2013)

(untitled) - Brandão, P.; Pineiro, M.; Pinho e Melo, T. M. V. D. (Eur. J. Org. Chem., 2019)

(untitled) - Matsunaga, S.; Kumagai, N.; Harada, S.; Shibasaki, M. (J. Am. Chem. Soc., 2003)

(untitled) - Tominaga, K.-i.; Sasaki, Y. (Synlett, 2002)

(untitled) - Morales-Nava, R.; Fernández-Zertuche, M.; Ordóñez, M. (Molecules, 2011)

(untitled) - Pulla, S.; Unnikrishnan, V.; Ramidi, P.; Sullivan, S. Z.; Ghosh, A.; Dallas, J. L.; Munshi, P. (J. Mol. Catal. A: Chem., 2011)

(untitled) - Liu, J.-M.; Peng, X.-G.; Liu, J.-H.; Zheng, S.-Z.; Sun, W.; Xia, C.-G. (Tetrahedron Lett., 2007)

(untitled) - Gabriele, B.; Salerno, G.; Brindisi, D.; Costa, M.; Chiusoli, G. P. (Org. Lett., 2000)

(untitled) - Zhou, M.; Zheng, X.; Wang, Y.; Yuan, D.; Yao, Y. (ChemCatChem, 2019)

(untitled) - Feroci, M.; Orsini, M.; Sotgiu, G.; Rossi, L.; Inesi, A. (J. Org. Chem., 2005)

(untitled) - Miller, A. W.; Nguyen, S. T. (Org. Lett., 2004)

(untitled) - Speranza, G. P.; Peppel, W. J. (J. Org. Chem., 1958)

(untitled) - Baronsky, T.; Beattie, C.; Harrington, R. W.; Irfan, R.; North, M.; Osende, J. G.; Young, C. (ACS Catal., 2013)

(untitled) - North, M.; Pasquale, R.; Young, C. (Green Chem., 2010)

(untitled) - Aoyagi, N.; Furusho, Y.; Endo, T. (Synthesis, 2020)

(untitled) - Martín, C.; Fiorani, G.; Kleij, A. W. (ACS Catal., 2015)

(untitled) - Shimojo, M.; Matsumoto, K.; Hatanaka, M. (Tetrahedron, 2000)

(untitled) - Shellhamer, D. F.; Davenport, K. J.; Hassler, D. M.; Hickle, K. R.; Thorpe, J. J.; Vandenbroek, D. J.; Heasley, V. L.; Boatz, J. A.; Reingold, A. L.; Moore, C. E. (J. Org. Chem., 2010)

(untitled) - Shellhamer, D. F.; Alexander, K. L.; Bunting, S. A.; Elwin, S. L.; Licata, C. J.; Milligan, J. C.; Robinson, R. D.; Shipowick, D. E.; Smith, L. B.; Perry, M. C. (Synthesis, 2015)

(untitled) - Dhar, D. N.; Murthy, K. S. K. (Synthesis, 1986)

(untitled) - Keshava Murthy, K. S.; Dhar, D. N. (Synth. Commun., 1984)

(untitled) - Murthy, K. S. K.; Dhar, D. N. (J. Heterocycl. Chem., 1984)

(untitled) - Lorincz, T.; Erden, I.; Näder, R.; de Meijere, A. (Synth. Commun., 1986)

(untitled) - Atmaca, U.; Yıldırım, A.; Taslimi, P.; Çelik, S. T.; Gülçin, İ.; Supuran, C. T.; Çelik, M. (J. Biochem. Mol. Toxicol., 2018)

(untitled) - Daryadel, S.; Atmaca, U.; Taslimi, P.; Gülçin, İ.; Çelik, M. (Arch. Pharm. (Weinheim, Ger.), 2018)

(untitled) - Atmaca, U.; Daryadel, S.; Taslimi, P.; Çelik, M.; Gülçin, İ. (Arch. Pharm. (Weinheim, Ger.), 2019)

(untitled) - Atmaca, U. (Tetrahedron, 2019)

(untitled) - Darù, A.; Roca-López, D.; Tejero, T.; Merino, P. (J. Org. Chem., 2016)

(untitled) - Laserna, V.; Fiorani, G.; Whiteoak, C. J.; Martin, E.; Escudero-Adán, E.; Kleij, A. W. (Angew. Chem., Int. Ed., 2014)

(untitled) - Scholz, K.-H.; Heine, H.-G.; Hartmann, W. (Justus Liebigs Ann. Chem., 1977)

(untitled) - Steinbauer, J.; Spannenberg, A.; Werner, T. (Green Chem., 2017)

(untitled) - Hu, N. X.; Aso, Y.; Otsubo, T.; Ogura, F. (J. Org. Chem., 1989)

(untitled) - Yang, X.; Bumbu, V. D.; Liu, P.; Li, X.; Jiang, H.; Uffman, E. W.; Guo, L.; Zhang, W.; Jiang, X.; Houk, K. N.; Birman, V. B. (J. Am. Chem. Soc., 2012)

(untitled) - Sukhanova, A. A.; Puchkin, I. A.; Vasil'ev, A. A.; Zlotin, S. G. (Tetrahedron: Asymmetry, 2017)

(untitled) - Miceli, C.; Rintjema, J.; Martin, E.; Escudero-Adán, E. C.; Zonta, C.; Licini, G.; Kleij, A. W. (ACS Catal., 2017)

(untitled) - Lebel, H.; Mamani Laparra, L.; Khalifa, M.; Trudel, C.; Audubert, C.; Szponarski, M.; Dicaire Leduc, C.; Azek, E.; Ernzerhof, M. (Org. Biomol. Chem., 2017)

(untitled) - Tanaka, S.; Gunasekar, R.; Tanaka, T.; Iyoda, Y.; Suzuki, Y.; Kitamura, M. (J. Org. Chem., 2017)

(untitled) - Tantillo, D. J. (J. Phys. Org. Chem., 2008)

Gaussian 09, Revision B.01 (Gaussian, Inc., 2009)

(untitled) - Zhao, Y.; Truhlar, D. G. (Theor. Chem. Acc., 2008)

(untitled) - Zhao, Y.; Truhlar, D. G. (Acc. Chem. Res., 2008)

(untitled) - Guleli, M.; Erdem, S. S.; Ocal, N.; Erden, I.; Sari, O. (Res. Chem. Intermed., 2019)

(untitled) - Gonzalez, C.; Schlegel, H. B. (J. Chem. Phys., 1989)

(untitled) - Gonzalez, C.; Schlegel, H. B. (J. Phys. Chem., 1990)

(untitled) - Miertuš, S.; Scrocco, E.; Tomasi, J. (Chem. Phys., 1981)

CYLview, version 1.0b (Université de Sherbrooke, 2009)